Map of scientific publications on administration in Latin America - Pérez-Campdesuñer, Reyner; Sánchez-Rodríguez, Alexander; García-Vidal, Gelmar; Martínez-Vivar, Rodobaldo (Revista Venezolana de Gerencia, 2023)
This research focuses on characterizing the orientation of the research that shows the contributions in the field of administrative sciences in Latin America. To do this, publications on Administrative Sciences by researchers in the region reported in Scopus were analyzed. After an initial review of all these publications, the sample was reduced to 87%, identifying the functions or areas of knowledge towards which they were oriented, their evolution over time, the sectors and countries where they were published, the collaboration networks between countries based on the development of the research and the main journals where they have been published. The results show that the administrative sciences are present in the epistemological development of Latin America, its conception and evolution correspond to the theoretical and methodological principles that established it as a science; They also reflect the existence of a vast network of collaboration in research in this field between countries in the region and beyond. At the same time, they show the need to strengthen the ties of collaboration between the most prolific researchers to strengthen the existence of an autochthonous school that responds to the particularities of the socioeconomic environment where they develop.